Diagnosis and Management of Bacterial Meningitis in the Paediatric Population: A Review - Tacon, Catherine L.; Flower, Oliver (Emergency Medicine International, 2012)
Paediatric bacterial meningitis is a neurological emergency which, despite advances in medical management, still has a significant morbidity and mortality. Over recent decades new vaccines have led to a change in epidemiology of the disease; however, it remains a condition that requires a high index of suspicion, prompt diagnosis, and early management in the emergency department. New laboratory techniques and clinical tools are aiding the diagnosis of bacterial meningitis, yet some controversies still exist in its management. This paper outlines the changing epidemiology of the disease, current diagnostic techniques as well as controversies and advances in the management of bacterial meningitis in the paediatric population.